DID JESUS FORBID AMBITION FOR GREATNESS IN LUKE 22:24–30? AN INTERCULTURAL RECONSIDERATION - Folarin, George O.; Ojelade, William Sunday (European Scientific Journal, ESJ, 2014)
This is an Intercultural study of aspiration for greatness in Luke 22:24-30 first in the initial context of the first century Roman culture, and then in the contemporary Western Nigerian cultural context. The study looks at the common scholarly argument that the disciples were contending for superiority among themselves and that Jesus used this incident to correct their fight for power. After re-examining the text in the two cultural contexts, the study concludes that there is nothing condemnatory of aspiration for power in the text, but that the text challenges Jesus’ disciples to use the power inherent in it for and in his service.